Game of thrones. Season 8 [compact disc] : music from the HBO series - Djawadi, Ramin; Djawadi, Ramin (WaterTower Music, 2019)
The score from Game of Thrones season eight, the final season of the award-winning HBO series, features 32 tracks by Emmy Award-winning and Grammy Award-nominated composer Ramin Djawadi. It includes the nine-minute opus The Night King, as well as an instrumental version of the emotional ballad Jenny of Oldstones, and a version of fan-favorite The Rains of Castamere featuring vocals by Serj Tankian, known as the lead vocalist of System of a Down.